2009
DOI: 10.1182/blood.v114.22.2376.2376
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Lenalidomide in Combination with Rituximab for Patients with CD5+/CD20+ Hematologic Malignancies Who Relapse or Progress After Rituximab. Interim Analysis.

Abstract: 2376 Poster Board II-353 Background: Patients with relapsed or refractory CLL/SLL and patients with mantle cell lymphoma (McL) have a poor prognosis. Overall response rate (ORR) to salvage therapy for refractory patients is approximately 10-30%, and survival benefit with current treatment approaches is limited. Phase II studies of single agent lenalidomide in patients with relapsed or refractory CLL revealed an ORR of 32-58% (7-17% CR), dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Mechanistically, they discovered that lenalidomide enhanced CD20-mAb-dependent apoptosis of the MCL cells by upregulating activation of caspase-3, -8, -9 and the cleavage of PARP, as well as enhanced ADCC by CD16 induction on NK cells [ 73 ]. An increase in NK-mediated ADCC is also implicated in the success of RTX and lenalidomide combination therapy in CLL and NHL, although unproven in vivo [ 74 , 75 ]. Ofatumumab, another anti-CD20 monoclonal antibody, binds to a different epitope and induces greater complement-dependent cytotoxicity and has shown evidence of activity in fludarabine and rituximab-refractory CLL [ 76 , 77 ].…”
Section: Immunomodulatory Drugs Increase Natural Killer Cell Recogmentioning
confidence: 99%
“…Mechanistically, they discovered that lenalidomide enhanced CD20-mAb-dependent apoptosis of the MCL cells by upregulating activation of caspase-3, -8, -9 and the cleavage of PARP, as well as enhanced ADCC by CD16 induction on NK cells [ 73 ]. An increase in NK-mediated ADCC is also implicated in the success of RTX and lenalidomide combination therapy in CLL and NHL, although unproven in vivo [ 74 , 75 ]. Ofatumumab, another anti-CD20 monoclonal antibody, binds to a different epitope and induces greater complement-dependent cytotoxicity and has shown evidence of activity in fludarabine and rituximab-refractory CLL [ 76 , 77 ].…”
Section: Immunomodulatory Drugs Increase Natural Killer Cell Recogmentioning
confidence: 99%
“…Investigators have recently reported results from using the combination of lenalidomide and rituximab for treatment for relapsed CLL. 77,78 The larger study reported an OR rate of 68% for the 60 patients enrolled, but there were no CRs. 77 Investigators concluded that lenalidomide plus rituximab was more effective than historically observed with single-agent lenalidomide, even though all patients had received prior rituximab therapy.…”
Section: Lenalidomidementioning
confidence: 93%